Assessment of stability of orthodontic mini-implants under orthodontic loading: A computed tomography study - Kamlesh Kumar Garg; Megha Gupta (Wolters Kluwer Medknow Publications, 2015)
Objectives: Miniscrews have been used in recent years for anchorage in orthodontic treatment. However, it is not clear whether the miniscrews are absolutely stationary or move when force is applied. This prospective clinical study was undertaken to evaluate the mobility of orthodontic miniscrews under orthodontic loading using computed tomography. Materials and Methods: Ten adult patients (7 females and 3 males with mean age of 19 years, 7 mm overjet) who required en masse retraction of upper and lower anterior teeth infirst premolar extraction spaces were included in this study. After initial alignment of anterior teeth, the 0.019" ×0.025" stainless steel archwire were placed in preadjusted edgewise appliance. The miniscrews (diameter - 1.3 mm, length - 7 mm) were inserted in between second premolar and thefirst molar in the maxilla (zygomatic buttress) and in mandible on the buccal side as direct anchorage. Immediately after placement of miniscrews without waiting period, NiTi coil springs (force of 150 g in the maxilla and 100 g in the mandible) were placed for the retraction. Denta Scans were taken immediately before force application (T1) and 6 months later (T2). The mean changes obtained at T1 and T2 in Denta Scans (axial plane, coronal plane, paraxial plane) were evaluated to determine any movement of different parts of miniscrews using one-way ANOVA test and Student's unpaired t-test. Results: On average, miniscrews were extruded and tipped forward significantly, by 1 mm at the screw head in the axial plane (Group III) and 0.728 mm in the coronal plane (Group IV). Tail of miniscrews showed average tipping of 0.567 mm in the axial plane (Group I) and 0.486 mm in the paraxial plane (Group V). Least average mobility was shown by screw body of 0.349 mm in the axial plane (Group II). Clinically, no significant mobility was observed. Conclusion: Miniscrews are a stable anchorage for orthodontic tooth movement but do not remain absolutely stationary like an endosseous implant throughout orthodontic loading although miniscrews might move according to placement site, orthodontic loading, and inflammation of peri-implant tissue. Waiting period between miniscrews placement and orthodontic loading does not significantly affect the miniscrew mobility so immediate loading can be recommended. To prevent hitting any vital organs because of miniscrew mobility, it is recommended that they can be placed in a nontooth-bearing area that has no foramen, major nerves, or blood vessel pathway, or in a tooth-bearing area allowing a 1.5 mm safety clearance between the miniscrew and dental root.